2016
DOI: 10.1002/stem.2387
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomic Study Reveals that Protein Kinase A Regulates Neural Stem Cell Differentiation Through Phosphorylation of Catenin Beta-1 and Glycogen Synthase Kinase 3β

Abstract: Protein phosphorylation is central to the understanding of multiple cellular signaling pathways responsible for regulating the self-renewal and differentiation of neural stem cells (NSCs). Here we performed a large-scale phosphoproteomic analysis of rat fetal NSCs using strong cation exchange chromatography prefractionation and citric acid-assisted two-step enrichment with TiO 2 strategy followed by nanoLC-MS/MS analysis. Totally we identified 32,546 phosphosites on 5,091 phosphoproteins, among which 23,945 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Protein phosphorylation is central to the understanding of downstream signaling pathways responsible for regulating stem cell functions. Quantitative phosphoproteomics has been used to study global signaling events in pluripotent, and cancer stem cells and new therapeutic targets have accordingly been proposed ( 59 62 ). To our knowledge, however, it has not been used before to assess the impact of inflammation on stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation is central to the understanding of downstream signaling pathways responsible for regulating stem cell functions. Quantitative phosphoproteomics has been used to study global signaling events in pluripotent, and cancer stem cells and new therapeutic targets have accordingly been proposed ( 59 62 ). To our knowledge, however, it has not been used before to assess the impact of inflammation on stem cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that same mechanism underlies the effects of ANDRO on the neural differentiation of ADSCs. By quantitative phosphoproteomic analysis, Wang et al [ 16 ] demonstrated that the phosphorylation of GSK-3 β and β -catenin is involved in the regulation of NSC self-renewal and differentiation. Their results showed that S552 on β -catenin and S9 on GSK-3 β play critical roles in activating the Wnt canonical pathway for determining the fate of NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway plays an important role in controlling neuronal differentiation, dendritic development, axonal outgrowth and guidance, neuronal plasticity, and the synaptic function in the adult nervous system [ 15 ]. Recently, a quantitative phosphoproteomic study has reported that the phosphorylation of catenin β -1 (CTNNB1) and GSK3 β regulates the differentiation of neural stem cells (NSCs) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish iridophores are specified and then differentiate beginning at 20 h post fertilization (hpf), as detected by purine nucleoside phosphorylase ( pnp4a ) expression [10]. As PKA signaling functions during neuron differentiation [22], we hypothesized that PKA signaling regulates differentiation of the iridophore precursors, iridoblasts. To test this hypothesis, we examined pnp4a expression in forskolin and H89-treated larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Embryos were fixed in 4% paraformaldehyde in phosphate-buffered saline at pH 7.2, and processed using standard protocols [21]. Digoxigenin-labeled probes for mitfa [7], foxd3 [22,23], and pnp4a [10] have been previously described. All imaging was done using a Nikon SMZ-1500 stereomicroscope equipped with a Digital Sight DS-Ri1 Digital Camera.…”
Section: Methodsmentioning
confidence: 99%